World Trade Center Site Exposure Duration Is Associated with Hippocampal and Cerebral White Matter Neuroinflammation - Chuan Huang; Minos Kritikos; Mario Serrano Sosa; Thomas Hagan; Alan Domkan; Jaymie Meliker; Alison C. Pellecchia; Stephanie Santiago-Michels; Melissa A. Carr; Roman Kotov; Megan Horton; Sam Gandy; et al. (Molecular Neurobiology, 2023)
Responders to the World Trade Center (WTC) attacks on 9/11/2001 inhaled toxic dust and experienced severe trauma for a prolonged period. Studies report that WTC site exposure duration is associated with peripheral inflammation and risk for developing early-onset dementia (EOD). Free Water Fraction (FWF) can serve as a biomarker for neuroinflammation by measuring in vivo movement of free water across neurons. The present case-controlled study aimed to examine associations between WTC site exposure duration as well as EOD status with increased hippocampal and cerebral neuroinflammation. Ninety-nine WTC responders (mean age of 56) were recruited between 2017 and 2019 ( N = 48 with EOD and 51 cognitively unimpaired). Participants were matched on age, sex, occupation, race, education, and post-traumatic stress disorder (PTSD) status. Participants underwent neuroimaging using diffusion tensor imaging protocols for FWF extraction. Region of interest (ROI) analysis and correlational tractography explored topographical distributions of FWF associations. Apolipoprotein-e4 allele ( APOE ε4) status was available for most responders ( N = 91). Hippocampal FWF was significantly associated with WTC site exposure duration ( r = 0.30, p = 0.003), as was cerebral white matter FWF ( r = 0.20, p = 0.044). ROI analysis and correlational tractography identified regions within the limbic, frontal, and temporal lobes. Hippocampal FWF and its association with WTC exposure duration were highest when the APOE ε4 allele was present ( r = 0.48, p = 0.039). Our findings demonstrate that prolonged WTC site exposure is associated with increased hippocampal and cerebral white matter neuroinflammation in WTC responders, possibly exacerbated by possession of the APOE ε4 allele.

The Watts Connectedness Scale: a new scale for measuring a sense of connectedness to self, others, and world - Rosalind Watts; Hannes Kettner; Dana Geerts; Sam Gandy; Laura Kartner; Lea Mertens; Christopher Timmermann; Matthew M. Nour; Mendel Kaelen; David Nutt; Robin Carhart-Harris; Leor Roseman (Psychopharmacology, 2022)
Rationale A general feeling of disconnection has been associated with mental and emotional suffering. Improvements to a sense of connectedness to self, others and the wider world have been reported by participants in clinical trials of psychedelic therapy. Such accounts have led us to a definition of the psychological construct of ‘connectedness’ as ‘a state of feeling connected to self, others and the wider world’. Existing tools for measuring connectedness have focused on particular aspects of connectedness, such as ‘social connectedness’ or ‘nature connectedness’, which we hypothesise to be different expressions of a common factor of connectedness. Here, we sought to develop a new scale to measure connectedness as a construct with these multiple domains. We hypothesised that (1) our scale would measure three separable subscale factors pertaining to a felt connection to ‘self’, ‘others’ and ‘world’ and (2) improvements in total and subscale WCS scores would correlate with improved mental health outcomes post psychedelic use. Objectives To validate and test the ‘Watts Connectedness Scale’ (WCS). Methods Psychometric validation of the WCS was carried out using data from three independent studies. Firstly, we pooled data from two prospective observational online survey studies. The WCS was completed before and after a planned psychedelic experience. The total sample of completers from the online surveys was N = 1226. Exploratory and confirmatory factor analysis were performed, and construct and criterion validity were tested. A third dataset was derived from a double-blind randomised controlled trial (RCT) comparing psilocybin-assisted therapy ( n = 27) with 6 weeks of daily escitalopram ( n = 25) for major depressive disorder (MDD), where the WCS was completed at baseline and at a 6-week primary endpoint. Results As hypothesised, factor analysis of all WCS items revealed three main factors with good internal consistency. WCS showed good construct validity. Significant post-psychedelic increases were observed for total connectedness scores (η2 = 0.339, p < 0.0001), as well as on each of its subscales ( p < 0.0001). Acute measures of ‘mystical experience’, ‘emotional breakthrough’, and ‘communitas’ correlated positively with post-psychedelic changes in connectedness ( r = 0.42, r = 0.38, r = 0.42, respectively, p < 0.0001). In the RCT, psilocybin therapy was associated with greater increases in WCS scores compared with the escitalopram arm ( η p 2 = 0.133, p = 0.009). Conclusions The WCS is a new 3-dimensional index of felt connectedness that may sensitively measure therapeutically relevant psychological changes post-psychedelic use. We believe that the operational definition of connectedness captured by the WCS may have broad relevance in mental health research.

Exploitative competition alters bee foraging and flower choice - Nicholas J. Balfour; Sam Gandy; Francis L. W. Ratnieks (Behavioral Ecology and Sociobiology, 2015)